2022
DOI: 10.1021/acssensors.1c02305
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metal Ion-Induced Cross-Linking of Photoelectrochemical Peptides and Circulating Proteins for Evaluating Cardiac Ischemia/Reperfusion

Abstract: Patients having experienced the ischemia-reperfusion process are particularly vulnerable to subsequent heart attacks because this process can induce myocardial fibrosis, hallmarked by the release of reactive oxygen species and some proteases, such as cathepsin G, into the circulating blood. If these risk indicators can be monitored from the peripheral serum, early diagnosis and intervention may become a reality. For this purpose, we have designed an assay of free copper ions and cathepsin G in serum using only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Flavonoids are pigments found in plants with their broad pharmacological spectrum as antioxidants, antiviral, anti-inflammatory, anticarcinogenic, antibacterial, neurotrophic, neuroprotective, and immune-stimulants ( Reddy et al, 2021 ). Various fruits, including strawberries, persimmons, apples, grapes, kiwis, peach, onions, lotus root, and cucumber contain fisetin (2–160 μg/g) ( Grynkiewicz and Demchuk, 2019 ; Hao et al, 2022 ). Several preclinical studies revealed that fisetin has potential benefits against neurological health complications and neurodegenerative diseases like AD, PD.…”
Section: Fisetin and Its Pharmacological Activitiesmentioning
confidence: 99%
“…Flavonoids are pigments found in plants with their broad pharmacological spectrum as antioxidants, antiviral, anti-inflammatory, anticarcinogenic, antibacterial, neurotrophic, neuroprotective, and immune-stimulants ( Reddy et al, 2021 ). Various fruits, including strawberries, persimmons, apples, grapes, kiwis, peach, onions, lotus root, and cucumber contain fisetin (2–160 μg/g) ( Grynkiewicz and Demchuk, 2019 ; Hao et al, 2022 ). Several preclinical studies revealed that fisetin has potential benefits against neurological health complications and neurodegenerative diseases like AD, PD.…”
Section: Fisetin and Its Pharmacological Activitiesmentioning
confidence: 99%
“…Due inaccessibility, this technique is the best option for analysis of the blood hemodynamic [33][34][35][36][37][38][39][40] . This The grid generation is also required for the control volume approach [41][42][43][44][45][46][47][48][49] . As depicted in Fig.…”
Section: Applied Technique For Modellingmentioning
confidence: 99%
“…Prolonged hyperglycemia leads to the promotion of oxidative stress which per se triggers free radical formation and lipid peroxidation. These features cause a prominent inflammatory response, apoptotic changes, and pathological conditions in cardiac tissue [ 2 , 10 , 11 ]. Considering the high metabolic activity in cardiomyocytes, it is logical to think that these cells are prone to injury following the production of free radicals and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%